Inhibitory Activities of 11 Antimicrobial Agents and Bactericidal Activities of Vancomycin and Daptomycin against Invasive Methicillin-Resistant Staphylococcus aureus Isolates Obtained from 1999 through 2006 - Holmes, Robert L. (American Society for Microbiology (ASM), 2008)
We assessed MICs and minimal bactericidal concentrations of vancomycin, daptomycin, and nine other antimicrobials against methicillin-resistant Staphylococcus aureus isolates obtained from 1999 through 2006. No vancomycin, daptomycin, or linezolid resistance was observed. Clindamycin, gentamicin, and ciprofloxacin resistance decreased significantly. No tolerance to vancomycin or daptomycin was observed, nor was MIC creep seen.